Ordovician–Silurian Chileida—First Post-Cambrian Records of an Enigmatic Group of Brachiopoda. (May 2014) - Holmer, Lars E.; Popov, Leonid; Bassett, Michael G.
Abstract : Brachiopods of the order Chileida have been recorded previously only from rocks of early to mid-Cambrian age (Botomian–Amgaian). They are typified by having a calcareous strophic shell with a delthyrium and colleplax, and these characters are shown to be present in species of the two new genera Tolen and Trifissura, from the Late Ordovician of Kazakhstan and the Silurian of Sweden and Britain, respectively. In specimens of Trifissura, the triangular colleplax is phosphatized secondarily by bacterial activity. It is suggested that the phosphatized colleplax represents an organic pad and that served as the original attachment structure of Trifissura by encrustation. Tolen and Trifissura represent the first post-Cambrian record of chileides from the Ordovician and Silurian; the new family Trifissuridae forms the first phylogenetic link between Cambrian chileides and Carboniferous–Permian isogrammides.